Acesso à Justiça: os meios estatais e não estatais para a desburocratização no Judiciário - Moraes, Sandra Regina de (2024)
This dissertation aims to be a study of the forms of access to justice, the possibilities for improving this service, the laws that support these possibilities, as well as a history of this access in Brazil. It is through the study of Cappelletti and Garth and the concept of renewing waves of access to justice that we begin to explore the current tools for this access to be effective and swift. In this way, we intend to address Justice 4.0 and discuss the Multiport Court as a way of solving the country's litigation culture. The use of Artificial Intelligence and the internet to speed up work and reduce distances are also factors to consider in today's law, so that they can increase access to justice. State apparatuses are included in the text in order to understand the importance of non-state means of expanding access to justice, especially for part of the population that was not covered by the Judiciary. Thus, by demonstrating the options citizens have when seeking justice, we intend to conclude that Brazilians already have at their disposal various ways of ensuring that everyone can have their demands heard and their disputes resolved